2007
DOI: 10.1002/ijc.22519
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of P53 stability in p53 mutated human and mouse hepatoma cells

Abstract: The tumor suppressor p53 is frequently mutated in cancer. We have investigated the regulation of P53 in p53 wild type mouse hepatoma cells (line 55.1c), in p53 heterozygeously mutated cells (56.1b) and in p53 defective cells (lines 56.1d, 70.4 and HUH7) under various experimental settings. The basal levels of P53 were low in 55.1c cells, but nuclear accumulation occurred upon UVirradiation. Similarly, UV-exposure induced stabilization of P53 in the heterozygeously p53 mutated 56.1b hepatoma cells. By contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…CHK2 has been found to be dispensable for p53-mediated cell cycle arrest [ 23 , 24 ]. We were interested in exploring a p53-independent role for CHK2 in inducing cell cycle arrest because the tumor suppressor p53 is frequently mutated in cancer cells and the Huh-7 HCC cell line used in this study is p53 defective [ 25 ]. Using antibodies specific for CHK2, Thr68-phosphorylated CHK2, p53, and Ser20-phosphorylated p53, we detected a time-dependent increase in the level of Thr68-phosphorylated CHK2 and no change in the level of total CHK2 in Huh-7 cells (Figure 5 , right panel set).…”
Section: Resultsmentioning
confidence: 99%
“…CHK2 has been found to be dispensable for p53-mediated cell cycle arrest [ 23 , 24 ]. We were interested in exploring a p53-independent role for CHK2 in inducing cell cycle arrest because the tumor suppressor p53 is frequently mutated in cancer cells and the Huh-7 HCC cell line used in this study is p53 defective [ 25 ]. Using antibodies specific for CHK2, Thr68-phosphorylated CHK2, p53, and Ser20-phosphorylated p53, we detected a time-dependent increase in the level of Thr68-phosphorylated CHK2 and no change in the level of total CHK2 in Huh-7 cells (Figure 5 , right panel set).…”
Section: Resultsmentioning
confidence: 99%
“…6A). Importantly, the Huh7 cell line carries a single p53 mutation (A:T→G:C at codon 220) and is p53 defective [44], [45]. Thus, it is possible that other transcription factors are involved in the HCV-mediated up-regulation of DR4, and further research is needed to identify the transcription factors involved in HCV-regulated DR4 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…HCC progression involves alterations in many signaling pathways, such as EGF-Ras-MAPK, AKT-mTOR, Jak-Stat and NF-kB cascades (Llovet et al , 2008). In addition, inactivating mutations of the tumor suppressor p53, or p53 loss of expression, are among the most frequent genetic events associated with hepatocyte transformation (Bressac et al , 1990; Hinds et al , 1987), and the dysregulation of p53-dependent genes have been observed in HCC (Hailfinger et al , 2007; Hsu et al , 1993). …”
Section: Resultsmentioning
confidence: 99%